What Darwin saw : the journey that changed the world - Schanzer, Rosalyn (Washington, D.C. : National Geographic, 2009)
Introduces children to the life of Charles Darwin, describing how his innovative theories on evolution changed how people view the world.
Includes bibliographical references and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Booklist, March 2009.
Bulletin (Center for Children's books), March 2009.
Keywords: Darwin, Charles, -- 1809-1882 -- Juvenile literature; Darwin, Charles, -- 1809-1882 -- Travel -- Juvenile literature; Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Travel; Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Travel; Naturalists -- England -- Biography -- Juvenile literature; Naturalists; Naturalists -- England -- Biography